STRATEGI DINAS PERHUBUNGAN DALAM MENGATASI KEMACETAN DI KOTA MANADO PROVINSI SULAWESI - WALEAN, ANDREW; KAUNANG, MARKUS; KIMBAL, MARTHEN (JURNAL ADMINISTRASI PUBLIK, 2019)
Congestion is a traffic problem faced by developing countries such as Indonesia and this alsooccurs in congested areas. Congestion that has often occurred in urban areas when the routine occurs,especially at times such as office hours, office hours, weekends and holidays. Many impacts that occur bycongestion that are negative. Based on the background of the problem, this study has the objective to findout and analyze the Transportation Department's Strategy in overcoming traffic congestion in the city ofManado. This research use desciptive qualitative approach. Data collection techniques were carried out withthree main activities, namely interviews, observation, and documentation. The results showed that theTransportation Department Strategy in overcoming traffic congestion in the city of Manado, is not yetmaximized. This can be seen from the Transportation Agency's Organizational Strategy. hallways and curbsthat block traffic flow cause traffic jams. Seen from the Program Strategy implemented by the government,it has run well, such as programs that carry out one-way traffic and installation of traffic signs, but in thiscase there are still weaknesses - among other things, at some points of the bottleneck there has been noincrease in traffic signs or have been damaged, causing congestion.Keywords: Strategy, Congestion